Infrastructure of pharmacies of the primary health care in the Brazilian Unified Health System:: Analysis of PNAUM – Services data - Leite, Silvana Nair; Manzini, Fernanda; Álvares, Juliana; Guerra Junior, Augusto Afonso; Costa, Ediná Alves; Acurcio, Francisco de Assis; Guibu, Ione Aquemi; Costa, Karen Sarmento; Karnikowski, Margô Gomes de Oliveira; Soeiro, Orlando Mário; Farias, Mareni Rocha (Revista de Saúde Pública, 2017)
OBJECTIVE: To characterize the infrastructure of the primary health care pharmacies of the Brazilian Unified Health System, aiming at humanizing the offered services. METHODS: This is a cross-sectional study, of quantitative approach, from data obtained in the Pesquisa Nacional de Acesso, Utilização e Promoção do Uso Racional de Medicamentos – Serviços, 2015 (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines – Services, 2015). Information on 1,175 pharmacies/dispensing units were gathered from direct observation and assessment of dispensing units installations conducted by trained researchers who used a standardized form. The analyzed variables refer to the physical structure of pharmacies or medicine dispensing units of the health units under research. RESULTS: The pharmacy area was greater than 14 m2 in 40.3% of the sampled units, highlighting those from Midwest (56.9%) and Southeast (56.2%) regions and those of Northeast, with only 23.3%. About 80.2% units had waiting rooms with chairs for patients, 31.8% of them had dispensing areas inferior to 5m2 , while in 46.2% these areas were superior to 10m2 . Bars were found in service counters in 23.8% of health units, thus separating the patient from the professional; 44.1% had internet access. In most units, the area of medicine storage had no refrigerator or freezer for their exclusive storage and 13.7% had a specific room for pharmaceutical consultation. CONCLUSION: Aiming at achieving care humanization and improving working conditions for professionals, the structuring of the environment of pharmacy services is necessary. This would contribute to the better qualification of pharmacy services, comprising more than medicine delivery. Data on the Northeast region indicated less favorable conditions to the development of adequate dispensing services. Based on the panorama pointed out, we suggest the expansion of stimulus concerning the physical structure of pharmaceutical services, considering regional specificities